2020
DOI: 10.3389/fonc.2020.559548
|View full text |Cite
|
Sign up to set email alerts
|

A Ticket to Ride: The Implications of Direct Intercellular Communication via Tunneling Nanotubes in Peritoneal and Other Invasive Malignancies

Abstract: It is well established that the role of the tumor microenvironment (TME) in cancer progression and therapeutic resistance is crucial, but many of the underlying mechanisms are still being elucidated. Even with better understanding of molecular oncology and identification of genomic drivers of these processes, there has been a relative lag in identifying and appreciating the cellular drivers of both invasion and resistance. Intercellular communication is a vital process that unifies and synchronizes the diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 95 publications
2
21
0
1
Order By: Relevance
“…We show that TNT enables mitochondria exchange and other cytoplasmic factors from the tumor cell into the non-tumor cells. Mitochondrial exchange via TNT is not a new concept, as previously published by several groups 12 , 22 , 58 , 63 . The function of the mitochondrial transfer was suggested but not demonstrated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We show that TNT enables mitochondria exchange and other cytoplasmic factors from the tumor cell into the non-tumor cells. Mitochondrial exchange via TNT is not a new concept, as previously published by several groups 12 , 22 , 58 , 63 . The function of the mitochondrial transfer was suggested but not demonstrated.…”
Section: Discussionmentioning
confidence: 93%
“…Seventh, TNT are positive for several TNT markers that do not present in filopodia, including TTHY1, GAP43, and protein 14-3-3γ 16 . Lastly, TNT and other similar structures defined by other groups 4 , 12 , 47 , 109 corresponded to tangled processes with both characteristic, open-ended, and enclosed; however, whether other names such as cytonemes and tumor microtubes correspond to TNT needs to be determined. Thus, the definition of TNT structure is strict and separate from other cellular processes, including filopodium, lamellipodium, and pseudopods.…”
Section: Methodsmentioning
confidence: 97%
“…Many studies have shown that mitochondrial transfer between tumor cells as a mechanism of metabolic adaptation promotes tumorigenesis, invasiveness and metastasis [96][97][98] . And preventing the formation of TNTs may be a novel approach to treat cancer 99,100 . Researchers showed that TNTs formation and the transfer of cargo between neuronal cells are regulated by the Wnt/Ca 2+ pathway, thus intervention of Wnt/Ca 2+ pathway may be a way to reduce TNTs-caused damage 101 .…”
Section: The Transfer Of Mitochondria Between Cellsmentioning
confidence: 99%
“…In addition, mitovesicles are a recently identified novel population of EVs of mitochondrial origin that contain abundant mitochondrial markers and reflect the alteration of pathophysiological processes where mitochondrial dysfunction occurs and are much smaller than native mitochondria [ 21 ]. TNTs are actin-based direct cell-to-cell communication channels that serve to transfer a variety of molecules and organelles, including mitochondria and exosomes, which are thought to be the main delivery route to transfer intact mitochondria in solid tumors [ 18 , 22 , 23 ]. EV- and TNT-mediated cell-to-cell communication between cancer cells and stromal cells, such as bone marrow-derived mesenchymal stem cells, fibroblasts and endothelial cells, is reported to play roles in alterations in cancer cell bioenergetics, chemoresistance, invasion and metastasis [ 16 18 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNTs are actin-based direct cell-to-cell communication channels that serve to transfer a variety of molecules and organelles, including mitochondria and exosomes, which are thought to be the main delivery route to transfer intact mitochondria in solid tumors [ 18 , 22 , 23 ]. EV- and TNT-mediated cell-to-cell communication between cancer cells and stromal cells, such as bone marrow-derived mesenchymal stem cells, fibroblasts and endothelial cells, is reported to play roles in alterations in cancer cell bioenergetics, chemoresistance, invasion and metastasis [ 16 18 , 22 , 23 ]. However, because a variety of cellular components, such as cellular proteins, lipids, mRNAs and microRNAs, are transferred via EVs and TNTs from stromal cells to tumor cells and vice versa [ 19 , 23 ], the exact functional roles of transferred mitochondria, particularly tumor-derived mutant mtDNAs, remain unknown.…”
Section: Introductionmentioning
confidence: 99%